Distribution Optimization Model: A Case Study of Mobile Handset Distribution System - Devi Prasad Ghosh , (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
The objective of the paper was to develop a decision making tool that mobile handset distribution company could use to derive a more efficient and effective distribution of handsets to its channel. The paper developed the problem definition, the formulation of LP model, the procedure is designed as a solution to the problem, and the outcome as benefits to the company is presented. Linear programming model is formulated that can be solved using commercial software. This paper demonstrates the potential for using linear programming in managing large-scale transportation and distribution problems. The model resulted in the creation of new metrics for measuring the performance, the model will help the company understand conditions that result in inventory shortages, and the model lead to the discovery of inefficiencies in company distribution strategy. The model is directly beneficial to any company in Mobile Handsets distribution. With a large proportion of handsets sales is accounted by online retailers direct to customers, the distribution of handsets not only defines the cost but also customer satisfaction by managing delivery time and return-of-handsets offer. The model is also applicable for cases in other industries which operates in multiple markets and have large variety of Stock Keeping Units (SKUs).